Work Values and Multidimensional Career Commitment on Perceived Career Success: Reassessing Hybrid Career Perspective - Erlin, Nia Ariyani; Syahrizal; Siregar, Tika Rahma Yani (Jurnal Mebis, 2025)
Perceived career success in employee career development has received much attention in recent years. Keeping that in mind, this research examines the relationship between intrinsic and extrinsic work values and perceived career success within a hybrid career orientation. This research also tests the mediating role of multidimensional career commitment, which includes career resilience, career planning, and career identity. The sample consisted of 322 civil servants working in government agencies in Indonesia. The SEM-AMOS analytical model was used to test the measurement and structural models. The findings of the research study indicated a positive correlation between intrinsic work value and perceived career success. Moreover, the relationship between intrinsic work values and perceived career success was found to be influenced by career resilience, career planning, and career identity. In contrast, no significant relationship was observed between extrinsic work values and perceived career success. However, extrinsic work values were negatively related to career resilience. This research suggests that human resource management practitioners can enhance career management by emphasizing multidimensional career commitment and intrinsic work values.